Effects of Lockdown Drills on Students’ Fear, Perceived Risk, and Use of Avoidance Behaviors: A Quasi-Experimental Study - Schildkraut, Jaclyn (Criminal justice policy review, 2022)
Although widely used in schools across the United States, little is known about the impact of lockdown drills, particularly related to psychological outcomes such as fear, perceived risk, and avoidance. This study utilized survey data collected over 3 timepoints—baseline, after the first lockdown drill, and following training and a second lockdown drill—from more than 10,000 students in a large urban school district. The results indicate that students were less fearful and perceived lower risk after participating in lockdown drills and emergency response training, although reported avoidance behaviors increased. Perceived school safety predicted less fear, risk, and avoidance, while perceived emergency preparedness predicted less fear and avoidance but higher risk. Implications for broader considerations for school administrators and policymakers related to emergency preparedness preparation, including drills and training, are offered with particular focus given to best practices for trauma mitigation.